2015
DOI: 10.2215/cjn.04860514
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of GFR Using β-Trace Protein in Children

Abstract: Background and objectives Sex may affect the performance of small molecular weight proteins as markers of GFR because of differences in fat mass between the two sexes. The hypothesis was that the diagnostic performance of b-trace protein, a novel marker of GFR, would be significantly better in boys than in girls.Design, setting, participants, & measurements GFR, height, weight, serum creatinine, and b-trace protein were measured in 755 children and adolescents (331 girls) undergoing 99 technetium diethylenetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The volume of distribution of cystatin C is most likely the extracellular volume (ECV), which correlates better with lean body mass than body surface area [9]. While BTP is produced in the coronary arteries (reviewed recently by Filler et al [10], the differing fat mass between the genders has been shown to affect BTP-based GFR estimates [2]. Its volume of distribution is unknown [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of distribution of cystatin C is most likely the extracellular volume (ECV), which correlates better with lean body mass than body surface area [9]. While BTP is produced in the coronary arteries (reviewed recently by Filler et al [10], the differing fat mass between the genders has been shown to affect BTP-based GFR estimates [2]. Its volume of distribution is unknown [10].…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly interested in the fact that there was no bias induced by gender. There is a significant difference in body fat between the genders during puberty [2]. An adjustment for gender must be made in order to accurately estimate GFR in children when using creatinine [2,3], cystatin C [4], and BTP [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…EM Yang et al [4] used the entire cohort to generate the formula. The authors could have divided their study participants into one cohort of 160 patients to generate the formula and a second cohort composed of the remaining patients to validate the formula, akin to other biomarker discovery studies [13,14]. There are five stages for biomarker development, and the later stages focus on epidemiologic concepts within a diagnostic, prognostic, and screening framework to determine if new markers will advance clinical care [15].…”
Section: Generalizability and Future Applicationmentioning
confidence: 99%
“…The impact of sex confirms our previous findings. 37,38 For B2M, there was no effect of sex, and the equation based on BTP and B2M was free of significant bias. Not unexpectedly, this study demonstrates that age, sex, and race are less influential for both these small-molecular-weight proteins in comparison to creatinine, but not cystatin C. Most importantly, the authors demonstrated that the coefficient of variation of B2M for sex was smaller than that of cystatin C, which is probably due to the increased fat mass of women because adipocytes are the only nucleated cells in the body that do not produce cystatin C. 24 The authors then combined B2M and BTP and the resultant formula had similar accuracy to the CKD-EPI creatinine-cystatin C equation.…”
mentioning
confidence: 93%
“…Currently, BTP measurement is generally used for the detection of cerebrospinal fluid leakage, 36 and only a few laboratories routinely offer serum BTP for the assessment of eGFR. 36,37,39 In addition, it is likely that each biomarker will have some populations in which it is particularly well or poorly suited. Both BTM and B2M appear to have some advantages over serum creatinine for GFR estimation, but systemic inflammation and other factors clearly have some influence on the production of small-molecular-weight proteins, making the utility of these novel biomarkers less certain in people with acute and chronic systemic inflammatory states.…”
mentioning
confidence: 99%